Effects of dynamic stretching on strength, muscle imbalance, and muscle activation - Costa, P. B.; Herda, T. J.; Herda, A. A.; Cramer, J. T. (Medicine & Science in Sports & Exercise, 2014)
Purpose: This study aimed to examine the acute effects of dynamic stretching on concentric leg extensor and flexor peak torque, eccentric leg flexor peak torque, and the conventional and functional hamstring-quadriceps (H:Q) ratios. Methods: Twenty-one women (mean ± SD age = 20.6 ± 2.0 yr, body mass = 64.5 ± 9.3 kg, height = 164.7 ± 6.5 cm) performed maximal voluntary isokinetic leg extension, flexion, and eccentric hamstring muscle actions at the angular velocities of 60°/s and 180°/s before and after a bout of dynamic hamstring and quadriceps stretching as well as a control condition. Results: Leg flexion peak torque decreased under both control (mean ± SE for 60°/s = 75.8 ± 4.0 to 72.4 ± 3.7 N·m, 180°/s = 62.1 ± 3.2 to 59.1 ± 3.1 N·m) and stretching (60°/s = 73.1 ± 3.9 to 65.8 ± 3.3 N·m, 180°/s = 61.2 ± 3.3 to 54.7 ± 2.6 N·m) conditions, whereas eccentric hamstring peak torque decreased only after the stretching (60°/s = 87.3 ± 5.1 to 73.3 ± 3.6 N·m, 180°/s = 89.2 ± 4.4 to 77.0 ± 3.4 N·m) intervention (P < 0.05). Stretching also caused a decrease in conventional H:Q (60°/s = 0.58 ± 0.02 to 0.54 ± 0.02, 180°/s = 0.67 ± 0.02 to 0.61 ± 0.03) and functional H:Q ratios (60°/s = 0.69 ± 0.03 to 0.60 ± 0.03, 180°/s = 1.00 ± 0.06 to 0.60 ± 0.03) (P < 0.05). Conclusions: Because dynamic stretching reduced concentric and eccentric hamstring strength as well as the conventional and functional H:Q ratios, fitness and allied-health professionals may need to be cautious when recommending dynamic rather than static stretching to maintain muscle force.